ChemInform Abstract: Controlled Synthesis of Porous Platinum Nanostructures for Catalytic Applications. Issue 31 (5th August 2014) - Cao, Yanqin; Zhang, Junwei; Yang, Yong; Huang, Zhengren; Nguyen, Viet Long; Nogami, Masayuki
Abstract Review: 107 refs.